Sport-based video game causes mental fatigue and impairs visuomotor skill in male basketball players - Faro, H.; de Sousa Fortes, L.; de Lima-Junior, D.; Barbosa, B. T.; Ferreira, M. E. C.; Almeida, S. S. (International Journal of Sport and Exercise Psychology, 2023)
This study verifies the prolonged use effect of a sport-based video game (SBV) on basketball players` visuomotor performance. Fourteen male national-level basketball players (24.3 ± 4.1 years; experience time: 6.5 ± 1.9 years) performed two baseline visits and two experimental conditions in a randomised and counterbalanced crossover study. They completed a baseline visuomotor task with and without a ball and were familiarised with the mental fatigue assessment. The experimental conditions consisted of playing an SBV and watching a documentary as control (CON) lasting 60-min each. Before and after experimental conditions, the participants performed a visuomotor task and response subjective rating of mental fatigue indicator measures (i.e., Visual Analogue Scale [VAS]), Stroop Test (i.e., accuracy and response time), and theta band from electroencephalogram. Accuracy decreased, and response time increased on visuomotor tasks with and without the ball, only for the SBV condition (p < 0.05). Subjective rating of mental fatigue (i.e., VAS), the response time on Stroop task, and theta band increased only for the SBV condition (p < 0.05). Mental fatigue induced by prolonged use of SBV impairs visuomotor performance in male basketball players, decreasing accuracy and significantly increasing response time.